The Effectiveness of Restorative Justice in Resolving Criminal Acts: Interaction Between Ocu Customary Law and Positive Law - Jzani, M. Rafsan (Magister Hukum Universitas Semarang, 2025)
This study aims to analyze the effectiveness of restorative justice in resolving criminal acts at the Kampar District Police, focusing on the interaction between Ocu customary law and positive law. This study is urgent due to the legal system's increasing reliance on culturally grounded mechanisms for resolving minor crimes, particularly in regions like Kampar, Riau, where local customs remain influential. Restorative justice is considered a more humane and culturally adaptive approach, especially when involving traditional mechanisms. This study uses a qualitative normative method supported by case studies and interviews with customary leaders and police officials. The results show that restorative justice is effectively applied in Kampar with the involvement of the Ocu customary law, promoting reconciliation, victim recovery, and offender accountability. The synergy between customary institutions and the police plays a critical role in resolving disputes peacefully. However, challenges remain in harmonizing customary practices with national legal standards, requiring legal reform and capacity building among law enforcement and customary leaders. This study contributes uniquely by empirically demonstrating a functional hybrid justice model at the police level in a customary law context. It highlights how restorative justice, rooted in local traditions, can operate effectively within Indonesia’s legal pluralism framework. This article recommends greater institutional support and legal recognition for customary-based restorative practices to enhance justice delivery in multicultural societies.